RETRACTED: Enhancing environmental education for individuals with health limitations - Popov Vitaly; Musika Oksana; Kobysheva Larisa (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001